Assessment of the influence of settlements on the intensity of traffic flows on public roads of public use (ADVANCES IN MECHANICAL ENGINEERING AND TRANSPORT, 2021)
The work is devoted to the development of effective methods for forecasting the traffic intensity of transport flows near the settlements of different groups of settlements. The analysis of literature sources showed that the development of feasibility studies and projects for the construction and reconstruction of highways, the formation of projects for the organization of road traffic is based on the laws of formation of traffic flows. The accuracy of forecasting the intensity of traffic flows can be significantly reduced near large cities, this is due to the peculiarities of the formation of freight and passenger flows on the approaches to large cities, the value of which increases as you approach the city. Finding the relationship between the actual value of traffic intensity and the place of its determination in relation to the location of the site to the city center (settlement) allows you to assess the degree of influence of the city on its value. The result of the research is to establish a mathematical description of the relationship between the traffic intensity of transport flows and the distance to the city center, which is provided in the form of a transformation using distance as a basis, which increases the relationship between them. The closeness of the connection between the traffic intensity of transport flows and the distance to the city center is established not only for large cities, but also for medium and small cities. The established relationship is indicative of all groups of settlements with different populations and confirms the impact of settlements on the intensity of traffic near them. Studies have shown that the result of assessing the impact of settlements on the intensity of traffic flows is described with sufficient accuracy by regression equations, in which the variables are parameters that characterize settlements, namely the distance from the center of the settlement and population. Statistical evaluation of the obtained models indicates the admissibility of their use to predict the intensity of traffic flows near settlements.Keywords: traffic intensity, traffic flow, degree of influence, distance, correlation, group of settlements, population, model.